Comparison of the Effects of Browning-Inducing Capsaicin on Two Murine Adipocyte Models - Montanari, Tommaso; Boschi, Federico; Colitti, Monica (Frontiers in Physiology, 2019)
The increasing prevalence of obesity and its associated comorbidities has gained attention in developing effective treatments and strategies that promote energy expenditure and the conversion of fat from a white to a brite phenotype. Capsaicin, bioactive component of chili peppers and a transient receptor potential channel vanilloid 1 (TRPV1) agonist, has been known to stimulate the process of thermogenesis. In this study, the effects of capsaicin were assessed on two murine cellular models by quantifying the dynamic of lipid droplets (LDs) and the expression of genes involved in adipocyte browning. Present findings demonstrated that treatment with norepinephrine or capsaicin combined with norepinephrine on 3T3-L1 cells and X9 cells significantly promoted the reduction of LDs area surface and size. The transcription of browning related genes such as uncoupling protein 1 (Ucp1), T-box transcription factor 1 (Tbx1), PR domain containing 16 (Prdm16), peroxisome proliferator-activated receptor γ coactivator 1α (Ppargc1a) and cell death- inducing DNA fragmentation factor A (DFFA)-like effector A (Cidea) was up-regulated by chronic capsaicin treatment on differentiated 3T3-L1 cells. Instead, X9 cells were significantly responsive only to the treatment with norepinephrine, used as positive control.